Struktura semantyczna pojęcia nadziei a prawdopodobieństwo zajścia jej przedmiotu. Studium eksperymentalne - Gurak, Monika (Filozofia Nauki, 2024)
The article presents an experimental study on the concept of hope. Definitions of hope recognize its two main semantic components: desire and a certain belief in the possibility of the fulfilment of the object of hope. Based on theoretical considerations, I propose a hypothesis that hope that p excludes certainty that p and certainty that not-p. Corpus analysis provided linguistic evidence in support of the thesis: there are numerous examples of collocations that suggest that the probability ascribed to the fulfilment of the object of hope may be extremely small or extremely high; however, it does not exceed the boundary conditions presented above. Nevertheless, in the corpora, there are also examples of the conjunction of hope and certainty that may suggest that not all Polish speakers consider these epistemic states mutually exclusive. The results of the experimental study on the ascription of hope depending on the subjective probability of the fulfilment of its object have shown that Polish speakers usually do not ascribe hope when they are certain that the object of hope will not be fulfilled, but they eagerly ascribe it when they are certain that it will.